STUDENTS’ ERROR IN TRANSLATING A NARRATIVE TEXT: AN ANALYSIS - Srikandini Narulita (Kantor Bahasa Kalimantan Timur, 2016)
The English narrative text is a language source translated into a target language, Indonesian. There were kinds of errors in translating English sentences, phrases, and lexical meanings. It used a methodology of descriptive qualitative content analysis. There are sentence, phrase, and lexical meaning errors in translating the English text into Indonesian. The students made sentence errors by missing to substitute the constituent of sentences, omitting the sentence constituent, and missing to transfer English sentence construction. The students made phrase errors by missing to translate noun, verb, adjective, and prepositional phrases. The students also made lexical meaning errors of words, phrases, and clauses. The most frequent errors were 154 frequencies of lexical meaning errors. The second was 76 frequencies of phrase errors. And the last was 65 frequencies of sentence errors. So, the total frequency of errors was 295 frequencies.